Case report: Dramatic response to alectinib in a lung adenosquamous carcinoma patient harbouring a novel CPE-ALK fusion - Qin, Yanyan; Li, Fei; Tan, Yuan; Duan, Qianqian; Zhang, Qin (Frontiers in Oncology, 2022)
Abstract Lung Adenosquamous carcinoma (ASC) is a rare histological subtype of lung cancer accounting for 0.4 %–4 % of all lung cancers. ASC is generally considered to be an aggressive cancer with poor prognosis. There is no specific standard treatment for ASC, and current treatment of ASC is relied on the guideline for non-small cell lung cancer (NSCLC). To date, only sporadic canonical EML4-ALK fusions have been reported in ASC patients, and the efficiency of ALK-TKI is still unclear in non-canonical ALK fusion positive ASC patients. Here we describe the case of a stage Ⅳ ASC patient harboring a novel CPE-ALK fusion detected via 74 genes panel analysis. Interestingly, the TP53 was wild-type and no another somatic mutation was found within 74 genes. In addition, immunohistochemical staining (IHC) also supports an oncogenic role for the CPE-ALK fusion. Based on these findings, the patient received alectinib 600 mg twice daily. After 4 months on treatment the patients achieved a radiological partial response (PR) and his symptoms were significantly relieved. Imaging showed that lesions of the patient were reduced, and the clinical evaluation was partial response (PR). To the best of our knowledge, this is the first report of a dramatic tumor response to alectinib in a patient with ASC harboring a CPE-ALK fusion. In addition, targeted NGS analysis may improve detection of ALK fusion in routine practice. Keywords: Lung Adenosquamous carcinoma; NGS; CPE-ALK; Alectinib;